Bail support schemes for adults - Hucklesby, Anthea (Book collections on Project MUSE., 2011)
This important book makes a valuable contribution to an under-researched area. It includes an evaluation of the Effective Bail Scheme (EBS) and discusses the potential for the wider development of bail support schemes and some of the questions and challenges posed by their use.